Integrasi Islamic Storytelling Menggunakan Media Televisi untuk Meningkatkan Perilaku Positif dan Atensi Anak dengan Gangguan Attention Deficit Hyperactivity Disorder (ADHD) - Putri, Oktarisanti Syahda; Iryanti, Shobah Shofariyani; Fuad, Ai Fatimah Nur (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2024)
Statistical data in Indonesia indicates that the population of school children suffering from ADHD is currently at 26,4 percent, meaning that 1 in 5 children and adolescents under the age of 18 experience mental health issues. At least, there are 16 million children with Attention Deficit Hyperactivity Disorder (ADHD). The subjects of this research are children aged 5 to 12 years who have ADHD. The aim of this research is to describe the impact of integrating Islamic storytelling through television media on children with ADHD. Research on children with ADHD is still limited in Indonesia. This study uses a qualitative model with case studies, literature reviews, field studies, observations, and interviews. The research concludes that the integration of Islamic storytelling in children with ADHD can help improve attention and mitigate impulsive behavior, promoting positive behavior in children with ADHD. The selected Islamic storytelling is tailored to the specific impulsive behaviors exhibited, such as addressing issues related to using inappropriate language.